X-linked Charcot Marie Tooth mutations alter CO2 sensitivity of connexin32 hemichannels - Butler, Jack; Dale, Nicholas (Frontiers in Cellular Neuroscience, 2023)
Connexin32 (Cx32) is expressed in myelinating Schwann cells. It forms both reflexive gap junctions, to facilitate transfer of molecules from the outer to the inner myelin layers and hemichannels at the paranode to permit action potential-evoked release of ATP into the extracellular space. Loss of function mutations in Cx32 cause X-linked Charcot Marie Tooth disease (CMTX), a slowly developing peripheral neuropathy. The mechanistic links between Cx32 mutations and CMTX are not well understood. As Cx32 hemichannels can be opened by increases in PCO2, we have examined whether CMTX mutations alter this CO2 sensitivity. By using Ca2+ imaging, dye loading and genetically encoded ATP sensors to measure ATP release, we have found 5 CMTX mutations that abolish the CO2 sensitivity of Cx32 hemichannels (A88D, 111–116 Del, C179Y, E102G, V139M). Others cause a partial loss (L56F, R220Stop, and R15W). Some CMTX mutations have no apparent effect on CO2 sensitivity (R15Q, L9F, G12S, V13L, V84I, W133R). The mutation R15W alters multiple additional aspects of hemichannel function including Ca2+ and ATP permeability. The mutations that abolish CO2 sensitivity are transdominant and abolish CO2 sensitivity of co-expressed Cx32WT. We have shown that Schwannoma RT4 D6P2T cells can release ATP in response to elevated PCO2 via the opening of Cx32. This is consistent with the hypothesis that the CO2 sensitivity of Cx32 may be important for maintenance of healthy myelin. Our data, showing a transdominant effect of certain CMTX mutations on CO2 sensitivity, may need to be taken into account in any future gene therapies for this condition.